KONSUMSI MEDIA INSTAGRAM SEBAGAI SUMBER INFORMASI KESEHATAN DALAM PENYEBARAN INFROMASI KESEHATAN STROKE - Azizah, Dinda Aiswara; Juariyah, J. (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
Social media plays a crucial role in raising public awareness of various health issues. Instagram is a popular social media platform and functions well in disseminating health-related information, including information about stroke. This study aims to determine how Instagram consumption as a source of health information influences the dissemination of stroke information. This study used a qualitative content analysis method on various posts containing information about stroke symptoms, prevention, and initial treatment. The results indicate that Instagram has great potential as a health education medium due to its visual, interactive, and easily accessible nature, which can increase public awareness about stroke. Various features such as feeds, stories, reels, hashtags, direct messages (DM), taplinks, and stickers enable faster and more engaging information delivery. However, the main challenge with information disseminated to a large audience is ensuring its accuracy and credibility. Therefore, it is crucial for users to further improve their digital literacy skills. It is crucial for users to be able to easily and wisely filter the health information they receive. Keywords: Instagram, Stroke Information, Media Consumption, Social Media, Stroke Education